The Design Process and the Building Site: Leonardo da Vinci at Milan Cathedral as a case study - Giulia Ceriani Sebregondi (Architectural Histories, 2022)
The involvement of Leonardo da Vinci (1452-1519) in the competition for the design of the dome of Milan Cathedral in 1487 offers a window onto many aspects of architectural practice and management in the early modern period. It allows us to investigate several features of the building site administration, the design process, and the complex decision-making processes of several large Italian building projects. Many written sources document the construction of the dome of Milan Cathedral, primarily administrative notes and book accounts. Only through a detailed aggregation and analysis of those data, given the long history of the building, can those aspects be philologically reconstructed. Up to now, the sources related to Leonardo’s involvement with the Milan dome have been analysed mainly for his ideas on architecture and to exalt his exceptionality, which has isolated the artist from his own time and his project from its background. This article re-reads this case study of the 1487 competition for the dome in the context of the cathedral's entire building history, to point out different aspects of architectural and management habits of early modern building projects, together with aspects of Leonardo’s design process.